CELLULAR OPEN RESOURCE (COR): current status and future directions. - Garny, A; Noble, D; Hunter, P; Kohl, P (2009)
The need for tools to aid the description and sharing of biological models was highlighted at the launch of the International Union of Physiological Sciences Physiome Project in 1997. This has resulted in the release, in 2001, of the CellML specifications (http://www.cellml.org/specifications/). CELLULAR OPEN RESOURCE (COR) was among the early adopters of this standard, eventually forming the first publicly available CellML-based modelling and collaboration environment. From the onset, COR was designed to provide an environment that could not only be used by experienced modellers, but also by experimentalists, teachers and students. It therefore tries to combine a user-friendly interface with a computationally efficient numerical engine. In this paper, we introduce the philosophy behind COR, explain its user interface and current functionality, including the editing and running of CellML files, highlight lessons learned from user feedback and problems experienced during the development of COR and conclude by exploring future development potential.